Análise de desempenho dos peptídeos sintéticos antimicrobianos in vitro e in sílico contra a linhagem colorretal HCT-116 - Oliveira, Francisco Laio de (2024)
Colorectal cancer (CRC) represents a significant public health challenge on a global scale, being the third most prevalent cancer in Brazil, excluding non-melanoma skin tumors. Due to its asymptomatic nature in the early stages, diagnosis often occurs in advanced stages, limiting the possibility of curative surgical intervention and requiring alternative treatments, such as chemotherapy. However, traditional chemotherapy agents, such as Fluorouracil (5-FU), can induce considerable adverse effects in patients, highlighting the urgency of developing cytotoxic compounds that minimize damage to the body. Synthetic peptides are emerging as a promising alternative due to their ability to be modified without losing their functionality. This allows for the removal of amino acid residues associated with toxicity. In this context, the present study aims to evaluate in vitro and in silico, the potential cytotoxic effect of two synthetic peptides, called PepGAT and PepKAA, as chemotherapeutic agents against the HCT-116 cell line. The cell invasion assays performed found a significant reduction of 70% and 75% in the invasive potential of cells treated with PepGAT and PepKAA peptides, respectively. The likely mechanism of action of these peptides is associated with interaction with the cell membrane, as evidenced by analysis of membrane prediction and generation of reactive oxygen species (ROS), decreased membrane irregularities, and increased ROS in subordinate cells treated with the peptides. Furthermore, it was observed that the peptides interfere with the cell cycle, resulting in a reduction in the S phase and an increase in the G2/M phase, which may indicate interruption of the formation of the mitotic spindle, and in the Sub-G1 phase, indicative of DNA fragmentation that leads to cell death, confirmed by the activation of caspases 3 and 7. In silico analyzes suggested that synthetic peptides can interact with the KRAS protein, causing conformational distortions in its three-dimensional structure and compromising its function. The results obtained demonstrate that the PepGAT and PepKAA peptides show potential therapeutic promise against CRC, demonstrating selectivity for tumor cells without causing damage to normal cells. These findings highlight the importance of these peptides as candidate cytotoxic agents that deserve further investigation for their clinical application.